2022
DOI: 10.1021/acs.jmedchem.2c00335
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Insights for Drug Repurposing and the Design of Hybrid Drugs for Alzheimer’s Disease

Abstract: The heterogeneity and complex nature of Alzheimer's disease (AD) is attributed to several genetic risk factors and molecular culprits. The slow pace and increasing failure rate of conventional drug discovery has led to the exploration of complementary strategies based on repurposing approved drugs to treat AD. Drug repurposing (DR) is a costeffective, low-risk, and efficient approach for identifying novel therapeutic candidates for AD treatment. Similarly, hybrid drug design through the integration of distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 146 publications
0
21
0
Order By: Relevance
“…54 Ex-vivo immunofluorescence and in vivo 19 F-MR imaging in rTg4510 mouse model revealed that Shiga-X35 colocalise with tau tangles and accumulate in the forebrain of Tg AD mouse. In vivo 19 F-MRI signal from AD mouse brain was significantly higher which distinguish AD from WT mouse. The accumulation of hyperphosphorylated tau inside the neuronal cells is an early event of tau pathology in AD that possibly change the cell surface markers.…”
Section: Tau Pet and Mr Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…54 Ex-vivo immunofluorescence and in vivo 19 F-MR imaging in rTg4510 mouse model revealed that Shiga-X35 colocalise with tau tangles and accumulate in the forebrain of Tg AD mouse. In vivo 19 F-MRI signal from AD mouse brain was significantly higher which distinguish AD from WT mouse. The accumulation of hyperphosphorylated tau inside the neuronal cells is an early event of tau pathology in AD that possibly change the cell surface markers.…”
Section: Tau Pet and Mr Imagingmentioning
confidence: 99%
“…MRI probes targeting tau pathology are limited, few probes are developed and evaluated in Tg mouse models. A novel buta-1,3-diene derived 19 F-MRI probe Shiga-X35 was developed targeting tau tangles for MR imaging. 54 Ex-vivo immunofluorescence and in vivo 19 F-MR imaging in rTg4510 mouse model revealed that Shiga-X35 colocalise with tau tangles and accumulate in the forebrain of Tg AD mouse.…”
Section: Tau Pet and Mr Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…43−50 Because of the AD drug development failures, new strategies like repurposing of drugs have emerged as a viable strategy with the potential to interfere with the underlying disease mechanisms of AD and slow its progression. 44 Due to rising problem of antibiotic resistance, repurposing of antibiotics for treating other disease seems to be a plausible option. Several antibiotics like rifampicin, minocycline, d-cycloserine, doxycline, and rifaximin and a combination of other antibiotics have shown antiamyloidogenic behavior in vitro and in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…To date, only two strategies are being used to treat AD patients: acetylcholinesterase inhibitors to maintain the level of acetylcholine in the brain and N -methyl- d -aspartate receptor antagonists to prevent excitotoxicity, but none of them alter the progression of disease . Over several years, other strategies have been studied to reduce or disrupt the Aβ assemblies, including immunotherapeutic vaccines, antibodies, peptides, , natural compounds, and repurposing drugs. Because of the AD drug development failures, new strategies like repurposing of drugs have emerged as a viable strategy with the potential to interfere with the underlying disease mechanisms of AD and slow its progression . Due to rising problem of antibiotic resistance, repurposing of antibiotics for treating other disease seems to be a plausible option.…”
Section: Introductionmentioning
confidence: 99%